Corporate University and Development of HR Street-Level Bureaucracy - Dedi Kusuma Habibie; Atika Ulfa Putri (Iapa Proceedings Conference, 2019)
The development of science and technology is now so rapid, globalization, industrial revolution 4.0, e-Government etc. Affect the functioning of the current bureaucracy, various efforts taken by the government to be able to adapt to changes, bureaucratic reform, good governance and various other approaches focusing on professional institutional development and bureaucratic human resources, until now the approach has continued and continues to look for various approaches that are deemed feasible in increasing the professionalism of bureaucratic human resources, especially at street-level bureaucracy which is directly in contact with the community.Corporate University approach (CU) in increasing the professionalism of street-level bureaucracy, what is offered by the CU approach and how this approach can develop street-level bureaucracy. This study uses the literature review method by paying attention to various scientific works that are considered important to explain the topics raised.